Hidden biodiversity revealed by collections-based research—Laboulbeniales in millipedes: genus Rickia - Santamaria, Sergi; Enghoff, Henrik; Reboleira, Ana Sofia (Phytotaxa, 2016)
Nine new species of the genus Rickia parasitizing Diplopoda are described: R. appendicifera from Iran on Chiraziulus, R. candelabriformis from Australia and New Zealand on several Spirostreptida, R. galatheae from New Zealand on Eumastigonus, R. gigas from Tanzania on ‘Spirostreptus’ and Archispirostreptus, R. lophophora from Tanzania on some genera of Spirostreptidae, R. obelostrepti from Tanzania on Obelostreptus, R. odontopygiidarum from Tanzania on Odontopygidae, R. platessa from Singapore and Thailand on Pachybolidae, and R. rhynchophora from Australia on Trigoniulus.  This nearly triples the previously known number of species of Rickia species on millipedes; all 14 species are treated in this study with photomicrographs, additional observations on previously described taxa and comments. A key to these species is also provided. The Laboulbeniales species were found on millipede specimens preserved mostly at the Natural History Museum of Denmark, from samples collected between 1916 to the present.